ANALISA DAYADUKUNG TANAH GAMBUT NAGASARIBU-HUMBANG HASUNDUTAN DDENGAN CAMPURAN KAPUR MELALUI PENGUJIAN KUAT GESER LANGSUNG DAN KUAT TEKAN BEBAS - Semangat Marudut Tua Debataraja (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2019)
Peat is categorized into soft soil that is difficult to be processed especially for road subgrade, causing it is always avoided by the related parties in construction project. Solution for this problem is stabilization or technical improvement of land. One of the ways to improve soil bearing capacity that has problem is adding or mixing lime and cement and others. In this research, testing of physical properties of soil was done (properties index) on stabilized soil, that soil is from Nagasaribu village – Humbang Hasundutan Regency. That soil was stabilized by mixing / adding lime in which the quantity varied between 5% , 10% and 15% to know the carrying capacity by the result of soil properties index testing, soil shear strength, and tile strength free soil. On laboratory reseach’s result conducted, it was found that soil is categorized into organic peat containing organic clay with water content is as many as 84.73%, soil specific gravity is as many as 1.661, filter analysis passes to the filter number 200 is as many as 90.27% meanwhile soil liquid limit is as many as 69.66%, plastis limit is as many as 15.08%, plastis limit is as many as 54.59%. Based on USCS qualification, the soil is categorized into peat because it has high plastis and organic, meanwhile based on AASHTO the soil is categorized intoA-7-6. Soil bearing capacity is as many as 0.04 t/m2 and after being added by the mixture of lime in highest variation (15%) so that the soil bearing capacity increases tobe 0.1 t/m2